Smart Intelligent Aircraft Structures (SARISTU) 2015
DOI: 10.1007/978-3-319-22413-8_51
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Door Surround Structure with Integrated Structural Health Monitoring System

Abstract: Structural health monitoring (SHM) based on Lamb waves, a type of ultrasonic guided waves, is a promising method for in-service inspection of composite structures. Lamb waves can be excited and received using a network of actuators and sensors, which are permanently attached to the structure. By analysing the sensor signals, different kinds of structural defects can be detected and located through the interaction of the Lamb waves. This paper presents the development and manufacturing of a full-scale composite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 4 publications
0
7
0
Order By: Relevance
“…Door surround structure(DSS) [21] has been correspondingly reinforced with skin, partition frame and long truss around the opening, and is a good composite cabin door opening reinforcement structure. The structure was gradually thickened in the skin around the door incision, along with a ladder-like door frame structure on the sides of the opening, each consisting of reinforced ribs between two C-shaped compartments and the compartment.…”
Section: Cabin Door Opening Reinforcement Designmentioning
confidence: 99%
“…Door surround structure(DSS) [21] has been correspondingly reinforced with skin, partition frame and long truss around the opening, and is a good composite cabin door opening reinforcement structure. The structure was gradually thickened in the skin around the door incision, along with a ladder-like door frame structure on the sides of the opening, each consisting of reinforced ribs between two C-shaped compartments and the compartment.…”
Section: Cabin Door Opening Reinforcement Designmentioning
confidence: 99%
“…However, the extra cost of printing the conductive tracks must be considered. It is noted that the SHM layer [34] and the SMART layer [35] were also tested in [33], while the application of a flexible printed circuit is also presented in [10].…”
Section: Inspection Approachmentioning
confidence: 99%
“…Compared to the wired case, the diagnostic film offers the advantage of im precision and repeatability for the sensor placement, weight reduction, flexibility to different geometries, and possibly automation of the sensorization process [16 ever, the extra cost of printing the conductive tracks must be considered. It is no the SHM layer [34] and the SMART layer [35] were also tested in [33], while the tion of a flexible printed circuit is also presented in [10].…”
mentioning
confidence: 99%
“…However, for piezoceramic sensors, the proposed solutions are in the form of a ready-made layer that can be installed onto the structure either during manufacture or assembly and will include sensors, wires, connectors and the protective layer. Examples of these solutions are the smart layer by Stanford (Qing et al 2009), Diagnostic film by Imperial College shown in Bekas et al 2018) and the integrated SHM layer (Schmidt et al 2016), just to name a few.…”
Section: Size/weight Restrictionsmentioning
confidence: 99%